Developing e-resources utilisation strategies for Tanzanian higher learning institutions: A case of Mzumbe University - Mosha, Goodluck E.; Siyao, Peter O.; Onyango, David N. (Dar es Salaam University Press (DUP), 2023)
This paper aims to examine the development of e-resources utilisation strategies for Higher Learning Institutions in Tanzania taking the case of Mzumbe University. Data for this study were collected from three major sources: five Higher Learning Institutions (HLIs) in Tanzania (UDSM, SUA, MUHAS, CBE, & NM-AIST), e-resources usage statistics from COTUL subscribed databases for the MU library and views from the MU library users. Usage statistics from COTUL subscribed e-databases provided quantitative data which were supplemented with experiences from five visited HLIs and views from MU internal stakeholder forums. The study outlined the roles and functions of all Mzumbe University organs in promoting and advocating the use of subscribed e-resources. The MU organs ranged from the university management, schools, faculties, and directorates including the library, institutes and the MU students’ organization. Specifically, MU Library was assigned the role of training users, creating online e-resource discussion forums, improving library websites, acquiring e-resources remote access software, promoting and advocating e-resources use, and employing knowledge ambassadors. The study identified challenges encountered in implementing the strategies which include poor ICT infrastructure, shortage of librarians with e-resources skills and interest, the meagre budget allocated to the library, insufficient specialized subject contents from subscribed databases, and poor cooperation between academic staff and the librarians. Since the library renders cross-cutting functions to the University, the task of promoting e-resources usage was recommended to be played by every organ at the University. The University is urged to speed up subscription /acquisition of e-resources remote access tools which will be enhancing e-resources utilisation. Additionally, the maximum utilisation of e-resources will be fully achieved by changing the mindset of lecturers and students from relying solely on print to e-resources. This study was not able to extract all usage statistics from the 24 databases at Mzumbe University because some database vendors particularly free databases do not release COUNTER statistics. Based on the findings of this study, Mzumbe University Library may: decide and inform COTUL on which e-resource databases to renew; propose measures to improve the usage of e-resources and lay down University-wide e-resource strategies to improve utilisation strategies. This paper is based on original usage statistics provided by the e-resource vendors in the COUNTER format and interviews administered to some selected respondents. Related literature has been reviewed and used, and appropriate citations and references have been acknowledged. The paper has been checked through Turnitin plagiarism detecting software.